Does the Implementation of SFAS 71 Affect Banks Loan Loss Provisioning Behavior and Equity Valuation? - Suriawinata, Iman Sofian; Zulfiati, Lies; Rusli, Devvy (Universitas Syiah Kuala, 2025)
Objective It has been several reporting years since the implementation of SFAS 71, which became effective on January 1, 2020. This study aims to investigate the effect of adopting SFAS 71 on banks loan loss provisioning behavior, as well as on the value relevance of SFAS 71 in assessing the quality of banks loan portfolios.Design/Methodology A moderated generalized least squares regression method is used to analyze the panel data from a sample of 40 publicly traded commercial banking companies from 2016 to 2022.Results SFAS 71 provides unintended opportunities for bank managers to engage in strategic income smoothing practices through loan loss provisioning. However, the loan loss provisions calculated under the SFAS 71 appear to give more useful information for capital market participants in assessing banks' loan portfolio quality and risk. Therefore, adopting SFAS 71 has a favorable impact on bank equity valuation.Research limitations/implications The study period relating to the implementation of SFAS 71 coincides with the COVID-19 pandemic era. Therefore, the results obtained in this study may be attributed to the combined effect of SFAS 71 and the pandemic. Future studies using banking data post-COVID-19 are strongly recommended.Novelty/Originality This paper is the first to empirically investigate the effect of the adoption of SFAS 71 on banks loan loss provisioning behavior as well as its value relevance relating to the quality and riskiness of banks loan portfolios. This study contributes to the understanding of both the benefits and the potential misuse of SFAS 71.